Peran BUMDes Jaya Makmur dalam Pemberdayaan Ekonomi Masyarakat melalui Kelompok Usaha Kerupuk Rambak “Nggodang Lawe” Rembang - Nafi'ah, Nur Kholishotun; Khoiriyah, Nur (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2025)
This study aims to analyze the role and impact of BUMDes Jaya Makmur in promoting community economic empowerment through the management of the “Nggodang Lawe” cracker business in Lambangan Wetan Village, Bulu District, Rembang Regency. The research employed a qualitative descriptive method with a case study approach, in which data were collected through interviews, observations, and documentation. The findings indicate that BUMDes Jaya Makmur plays a significant role in enhancing the community’s capacity and self-reliance through five stages of economic empowerment: awareness, planning, implementation, evaluation, and development. The cracker business program not only increases income and skills but also expands access to capital, training, and markets. Moreover, the program has encouraged active participation among community members—particularly women—in productive economic activities. Overall, BUMDes Jaya Makmur has successfully developed a sustainable community-based empowerment model that strengthens the local economic structure and serves as a driving force for rural economic independence.